CRESST cryogenic dark matter search - Cozzini, C; Angloher, G; Bucci, C; von Feilitzsch, F; Frank, T; Hauff, D; Henry, S; Jagemann, T; Jochum, J; Kraus, H; Majorovits, B; Ninkovic, J; et al. (2005)
The CRESST Phase II experiment at Gran Sasso is using 300 g scintillating CaWO4 crystals as absorbers for direct WIMP (weakly interactive massive particles) detection. The phonon signal in the CaWO4 crystal is registered in coincidence with the light signal, which is measured with a separate cryogenic light detector. The absorber crystal and the silicon light detector are read out by tungsten superconducting phase transition thermometers (W-SPTs). As a result an active discrimination of the electron recoils against nuclear recoils is achieved. Results on the properties of the detector modules and on the WIMP sensitivity are presented. (C) 2005 Published by Elsevier B.V.